Growth response of four freshwater algal species to dissolved organic nitrogen of different concentration and complexity. (18th May 2015) - Fiedler, Dorothea; Graeber, Daniel; Badrian, Maria; Köhler, Jan
Summary Dissolved organic nitrogen (DON) compounds dominate the nitrogen pool of many lakes, but their importance as nitrogen sources for freshwater phytoplankton is not fully understood. Previous growth experiments demonstrated the availability of urea and amino acids but often at unnaturally high concentrations. The importance of complex DON compounds for growth of common phytoplankton species is still unknown. This study compared changes in chlorophyll a concentrations of freshwater phytoplankton with different DON compounds of varying complexity (urea, dissolved free (DFAA) and combined amino acids (DCAA), natural organic matter (NOM)) or with nitrate as the sole nitrogen source. Monocultures of Chlamydomonas spp., Cyclotella meneghiniana, Microcystis aeruginosa and Anabaena flos‐aquae were incubated with dissolved nitrogen compounds at concentrations ranging from 0.01 to 0.5 mg N L−1, which is within the range of concentrations that have been observed in a typical Central European shallow, eutrophic lake. All studied species grew in all treatments, but their biomass gains decreased with increasing complexity of the N source. Urea addition caused the strongest biomass increase, only in some cases matched by nitrate. Urea was also utilised over a longer time period than any other compound, including nitrate. The assumed delay in availability with increasing compound complexity was not supported by this experiment. The studied species differed in their temporal response and their compound preferences. Therefore, DON composition can influence biomass and structure of phytoplankton communities. These experiments demonstrate the importance of the main DON compounds for phytoplankton growth when no inorganic nitrogen is available. DON should in future be included in nitrogen budget calculations and management strategies, especially in relation to reducing nitrogen loading.